2008
DOI: 10.1016/j.difgeo.2007.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Two Gauss–Bonnet and Poincaré–Hopf theorems for orbifolds with boundary

Abstract: DateThe final copy of this thesis has been examined by the signatories, and we find that both the content and the form meet acceptable presentation standards of scholarly work in the above mentioned discipline.iii Seaton, Christopher W. (Ph.D., Mathematics)Two Gauss-Bonnet and Poincaré-Hopf Theorems for Orbifolds with Boundary Thesis directed by Assoc. Prof. Carla FarsiThe goal of this work is to generalize the Gauss-Bonnet and Poincaré-Hopf Theorems to the case of orbifolds with boundary. We present two such … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…As H * orb (Q) and H * orb (E) are defined to be sums of the de Rham cohomology of the sectors of the respective orbifolds, the sum, ι * , is then clearly an isomorphism of additive groups. ✷ Finally, we note that any characteristic class c (see [2] Proposition 4.3.4) or orbifold characteristic class c orb (see [5] Appendix B) defined by the ChernWeil construction for vector bundles can be extended to the case of bad orbifold vector bundles. Note that the definition of orbifold characteristic classes c orb (E) applies the Chern-Weil construction to connections on the bundleẼ overQ.…”
Section: Now Consider the Mapmentioning
confidence: 99%
See 2 more Smart Citations
“…As H * orb (Q) and H * orb (E) are defined to be sums of the de Rham cohomology of the sectors of the respective orbifolds, the sum, ι * , is then clearly an isomorphism of additive groups. ✷ Finally, we note that any characteristic class c (see [2] Proposition 4.3.4) or orbifold characteristic class c orb (see [5] Appendix B) defined by the ChernWeil construction for vector bundles can be extended to the case of bad orbifold vector bundles. Note that the definition of orbifold characteristic classes c orb (E) applies the Chern-Weil construction to connections on the bundleẼ overQ.…”
Section: Now Consider the Mapmentioning
confidence: 99%
“…In previous work (see [5] and [6]), we have defined an orbifold Euler class in Chen-Ruan orbifold cohomology (note that in [5], the definition of an orbifold vector bundle was taken to be that of a good orbifold vector bundle). In [6], it was demonstrated that when all of the local groups are cyclic, this class acts as a complete obstruction to the existence of nonvanishing tangent vector fields.…”
Section: Application: the Orbifold Euler Class Of A Bad Orbifold Vectmentioning
confidence: 99%
See 1 more Smart Citation
“…If the orbifold Q is closed, we let χ ES (Q) denote the Euler-Satake characteristic of Q (see [15] where this number is called the Euler characteristic of Q as a V -manifold or [16] where this quantity is denoted 1 by χ orb (Q)). Recall that the Euler-Satake characteristic is most easily defined in terms of a simplicial decomposition T of Q such that the isomorphism class of the isotropy group is constant on the interior of each simplex (it is shown in [10] that such a simplicial decomposition always exists).…”
Section: 3mentioning
confidence: 99%
“…Satake's Euler characteristic as a V -manifold) is a trivial consequence of Satake's Poincaré-Hopf Theorem in [15]. In [16,Corollary 3.4], the second author offered a different Poincaré-Hopf theorem, demonstrating that a nonvanishing vector field also implies that the Euler characteristic of the underlying topological space of Q vanishes. However, the converse of both of these statements is false; it is easy to construct examples of orbifolds such that both characteristics vanish, yet whose singular strata force any vector field to vanish (see [17]).…”
Section: Introductionmentioning
confidence: 99%